2014
DOI: 10.4038/slja.v22i1.6239
|View full text |Cite
|
Sign up to set email alerts
|

Role of tapentadol in pain management

Abstract: This article reviews tapentadol, a novel centrally-acting opioid analgesic that exerts its analgesic effects through muopioid receptor agonism and additionally via noradrenaline reuptake inhibition and so potentially has a role in the treatment of both nociceptive and neuropathic pain. Appropriate management of acute, chronic and cancer pain remains a considerable challenge for health-care providers. The physiological and psychological effects of uncontrolled pain lead to unnecessary suffering and financial lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…Tramadol is metabolised to an active O-desmethyl metabolite which is responsible for these side effects. [ 8 18 19 ] Several authors have observed an increased incidence of PONV and sedation with tramadol. [ 4 9 ] Sedation was observed in six patients in tramadol group and none in tapentadol group ( P = 0.027) in this study; nevertheless, tapentadol appears to have a better central nervous system and gastrointestinal tolerability profile owing to lack of significant serotonergic activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tramadol is metabolised to an active O-desmethyl metabolite which is responsible for these side effects. [ 8 18 19 ] Several authors have observed an increased incidence of PONV and sedation with tramadol. [ 4 9 ] Sedation was observed in six patients in tramadol group and none in tapentadol group ( P = 0.027) in this study; nevertheless, tapentadol appears to have a better central nervous system and gastrointestinal tolerability profile owing to lack of significant serotonergic activity.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 9 ] Sedation was observed in six patients in tramadol group and none in tapentadol group ( P = 0.027) in this study; nevertheless, tapentadol appears to have a better central nervous system and gastrointestinal tolerability profile owing to lack of significant serotonergic activity. [ 8 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been advised not to use tapentadol when the patient has CNS and/or respiratory depression. [ 12 ] Tapentadol has no active metabolites. The respiratory rate and oxygen saturation were similar between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Ninguno de los metabolitos contribuye a la actividad analgésica. 11 Tapentadol es 18 veces menos potente que la morfina para unirse al receptor opioide μ humano y 2-3 veces menos potente para producir analgesia en los modelos animales, lo cual es consistente con su mecanismo de acción combinada. En modelos preclínicos, la actividad analgésica debida a los agonistas opioides del receptor μ de tapentadol se puede modular mediante antagonistas selectivos de los receptores opioides μ (por ej., naloxona), mientras que la recaptación de la inhibición de noradrenalina es sensible a los moduladores de norepinefrina.…”
Section: Introductionunclassified